2023
DOI: 10.3390/biomedicines11041022
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety and Feasibility of Superior Vena Cava Isolation in Patients Undergoing Atrial Fibrillation Catheter Ablation: An Up-to-Date Review

Abstract: Pulmonary vein isolation (PVI) is the cornerstone in atrial fibrillation (AF) ablation; yet, the role of arrhythmogenic superior vena cava (SVC) is increasingly recognized and different ablation strategies have been employed in this context. SVC can act as a trigger or perpetuator of AF, and its significance might be more pronounced in patients undergoing repeated ablation. Several cohorts have examined efficacy, safety and feasibility of SVC isolation (SVCI) among AF patients. The majority of these studies ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“… 2 Moreover, SVC cardiomyocytes are influenced by autonomic innervation, and it has been demonstrated that the adjacent aortocaval ganglion preferentially triggers SVC ectopic beats. 3 As a result of the above, adjunctive SVC isolation (SVCI) has been performed, in addition to PVI, in certain groups of patients undergoing ablation for AF. 4–7 The procedure, however, can be associated with complications including stenosis of the vein, phrenic nerve injury (PNI), and sinus node dysfunction (SND).…”
mentioning
confidence: 99%
“… 2 Moreover, SVC cardiomyocytes are influenced by autonomic innervation, and it has been demonstrated that the adjacent aortocaval ganglion preferentially triggers SVC ectopic beats. 3 As a result of the above, adjunctive SVC isolation (SVCI) has been performed, in addition to PVI, in certain groups of patients undergoing ablation for AF. 4–7 The procedure, however, can be associated with complications including stenosis of the vein, phrenic nerve injury (PNI), and sinus node dysfunction (SND).…”
mentioning
confidence: 99%